Effectiveness of High Intensity Interval Training (HIIT) in Improving Athlete Performance: A Literature Review - Sari, Liliana Puspa; Karo Karo, Alan Alfiansyah Putra; Rida, Akifah Khansa Zikrillah (Jurnal Pendidikan Jasmani (JPJ), 2024)
This study aims to determine effectiveness of high intensity interval training (HIIT) in improving athlete performance using a literature review approach. PRISMA standards for systematic reviews and meta-analyses were followed in this review investigation. Studies had to be published from 2022 to June 2024. In the search procedure, the following keywords were used: (1) HITT; (2) athlete performance. Scopus search engine was used in the data source of this study. Seventeen articles were created from the 121 search results in the database that were modified to meet the requirements. Research shows that HIIT can lead to significant improvements in various aspects of physical fitness, such as maximal oxygen uptake (VO2max), functional physical performance, fitness indices, and agility.